2018
DOI: 10.1093/biolre/ioy162
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 increases inflammatory damage inEscherichia coli-infected bovine endometrial tissue in vitro via the EP4-PKA signaling pathway†

Abstract: Endometritis is the most common bovine uterine disease following parturition. The role of prostaglandin E2 (PGE2) in the regulation of endometrial inflammation and repair is well understood. Excess PGE2 is also generated in multiple inflammatory diseases, including endometritis. However, it remains unclear whether PGE2 is associated with pathogen-induced inflammatory damage to the endometrium. To clarify the role of PGE2 in pathogen-induced inflammatory damage, this study evaluated the production of PGE2, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Hence, it does not entirely block the arachidonic pathway from arachidonic acid metabolism via the TXA2S, PGI2S, PGF2S and PGD2S enzymes. Arachidonic acid levels are reduced with MF63, so there may be less CFTR inhibition 61 . This is important, as arachidonic acid levels are known to be elevated in CF patients 60 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it does not entirely block the arachidonic pathway from arachidonic acid metabolism via the TXA2S, PGI2S, PGF2S and PGD2S enzymes. Arachidonic acid levels are reduced with MF63, so there may be less CFTR inhibition 61 . This is important, as arachidonic acid levels are known to be elevated in CF patients 60 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress leads to an excessive accumulation of reactive oxygen species, such as NO and PGE 2 , in activated macrophages that has been observed in both acute and chronic inflammation in a number of disease conditions, including atherosclerosis, obesity and arthritis (31)(32)(33). Inhibition of NO production and PGE 2 accumulation modulates the inflammatory response in macrophages, leading to the reduction of swelling and redness at the infection site (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we report that increased levels of leptin in the lung result in the upregulation of the inflammatory proteins cPLA2α and COX-2 and promote the accumulation of leukocytes. It is suggested that the expression of cPLA2α or COX-2-dependent prostaglandin E2 (PGE2) exacerbates Streptococcus pneumoniae or Escherichia coli-infected damage to the lung and endometrium [35,36]. Moreover, persistent chronic inflammation leads to fibrosis [37,38].…”
Section: Discussionmentioning
confidence: 99%